Trends in Journalism: A Special Study on Twitter - Jothi, P Sri (Journal of Advanced Research in Journalism & Mass Communication, 2018)
With the development of new mass media, the appearances and approaches of communication have become more specialised. In a country like India, so vast and varied, traditional mass media alone does not constitute the communication channels, even though modern mass media like websites, facebook, twitter, blogs, instagram and whatsapp plays a major role in communication. For the past two decades, information and communication technology activities have gained momentum in India. Efforts have been made from both governmental and non-governmental platforms to enhance public understanding of invariable information through various activities. But recently the impact is created due to the social media like facebook, twitter, blogs and forums etc. Many recent issues have created such impact in the society specially among the urban people and little effects among the rural community. Therefore the trend of making news and collecting information platform have been changed due to the convergence of media today. Thus the study is proposed to analyse and discuss the trends in journalism especially focused on collecting information by the reporters, journalist to make news. This entailed to analyse and find the drift of news making through twitter in the current scenario of digital communication. How to cite this article: Jothi PS. Trends in Journalism: A Special Study on Twitter. J Adv Res Jour Mass Comm 2018; 5(4): 154-156. DOI: https://doi.org/10.24321/2395.3810.201831